Singapore as a regional Islamic Hub in the nineteenth century - Khairul Ikhwan Ridzwan (2018)
This thesis investigates Singapore’s status and role as a nineteenth century regional Islamic Hub. Its purpose is to unravel and subsequently shed light on the circumstances, factors and actors that perpetuated Singapore’s status as the pre-eminent center of Islam in the region. The study begins with an examination of the annual Islamic pilgrimage to Mecca, the Hajj, and Singapore’s role as both a transit and staging point for Muslims from all around the region. This includes a brief overview of Dutch policies that drove its Muslim subjects to Singapore in order to undertake the Hajj. It also details the native actors that perpetuated Singapore’s status as a pilgrim hub through their active recruitment efforts and their collaboration with major shipping companies. The next chapter deals with Islamic printing and how the innovative practices of publishers essentially transformed Singapore into a regional hub of Islamic printing and publishing. Finally, the last chapter explores the role of mosques in Singapore and how they were responsible for propagating the spread of Islamic knowledge into the region as well as various forms of Islamic sects and doctrines. To date, no comprehensive study on Singapore’s status and role as an Islamic Hub during the nineteenth century exists.